PELAKSAAN TUGAS DAN WEWENANG BPJS DALAM PEMBERIAN JAMINAN SOSIAL TENAGA KERJA TERHADAP PERUSAHAAN YANG MEMENUHI SYARAT DI KOTA PEKANBARU BERDASARKAN UNDANG–UNDANG NOMOR 24 TAHUN 2011 TENTANG BADAN PENYELENGGARA JAMINAN SOSIAL - M. Kharisma Andreas; Evi Deliana; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Social Security Administering Agency (BPJS) Pekanbaru Branch throughout 2016 noted, already 1135 companies in Pekanbaru register its employees. Although the numbers are quite fantastic, but apparently not all companies listed. Because of the record BPJS, the total company ex Jamsostek alone there are about 1807 companies. This shows the company ex Jamsostek there who have not enrolled employees in BPJS employment of about 672 companies.The type of research used in the writing of this law is a sociological legal research that is a study of the effectiveness of the current law or research on the identification of law. Meanwhile, if viewed from the nature of this research is descriptive. This study uses primary data that is data obtained from the field through interviews and secondary data ie data that has been so.The results of this study is the implementation of duties and authority BPJS in the provision of social security workers against companies eligible in the city of Pekanbaru is in accordance with Article 10 and Article 11 of Law Number 24 Year 2011 is the task of BPJS which among other things is to do and receive registration of participants, collecting and managing participant data, receiving government contributions, collecting and collecting contributions from participants and employers, providing information to participants, managing social security funds for the benefit of participants, collecting and managing data of social security program participants. BPJS's authority, among others, is as follows: collect contributions to any company that enrolls employees as BPJS participants, supervises and inspects the compliance of participants and employers in fulfilling their obligations and imposing administrative sanctions on the participants, making agreements with health facilities on large payments of health facilities referring to tariff standards established by the Government, cooperating with other parties in the context of administering social security programs, and reporting the employer to the competent authority regarding non-compliance in fulfilling obligations. Barriers BPJS in carrying out social security of labor to eligible companies in Pekanbaru City is still quite a lot of companies that do not register their workers and the delay in payment contributions in the program BPJS Employment. Companies that do not register their employees in the Employment BPJS program will be given a written warning and if ignored this written warning will be given administrative sanctions in the form of not getting certain public services one of them with the revocation of business license on demand.Keywords: BPJS Employment, Social Security, Manpower.